Excitation mechanisms and effects of dopant concentration in Gd2O2S : Tb3+ phosphor - da Silva, Alison Abreu [UNESP]; Cebim, Marco Aurelio [UNESP]; Davolos, Marian Rosaly [UNESP] (Elsevier B.V., 2008)
Gadolinium oxysulfide powders doped with different Tb3+ concentrations were prepared from sulfur vaporization on rare earths' basic carbonate precursors. Single-phase Gd2O2S samples were obtained, with Tb3+ doping up to 9 at%. The study of the excitation mechanisms revealed that the Tb3+ emission might occur after the direct Tb3+ excitation either by energy transfer from Gd3+ or from the phosphor host. The characteristic terbium emission lines were observed, resulting from the radiative decay from D-5(3) or D-5(4), to F-7(j) levels. The cross-relaxation phenomenon was observed and its effects on the materials emission color were discussed based on the CIE diagram. By using time-resolved spectroscopy, D-5(3) -> F-7(J) and D-5(4) -> F-7(J) transitions were separated. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: scintillator; luminescence; cross relaxation; emission tuning